2011
DOI: 10.1136/tc.2010.039537
|View full text |Cite
|
Sign up to set email alerts
|

Social responsibility in tobacco production? Tobacco companies' use of green supply chains to obscure the real costs of tobacco farming

Abstract: Background Tobacco companies have come under increased criticism because of environmental and labor practices related to growing tobacco in developing countries. Methods Analysis of tobacco industry documents, industry web sites and interviews with tobacco farmers in Tanzania and tobacco farm workers, farm authorities, trade unionists, government officials and corporate executives from global tobacco leaf companies in Malawi. Results British American Tobacco and Philip Morris created supply chains in the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 30 publications
0
49
0
1
Order By: Relevance
“…Thus research that suggests that tobacco farmers are pauperised by low prices under contract farming18 or that tobacco engenders high social and environmental costs17 does so without a clear overview of other comparable crop value chains in specific regions. The implicit suggestion that tobacco alone causes such issues (although potentially accurate) is often under-evidenced.…”
Section: Existing Approaches To Researching Tobacco Productionmentioning
confidence: 99%
“…Thus research that suggests that tobacco farmers are pauperised by low prices under contract farming18 or that tobacco engenders high social and environmental costs17 does so without a clear overview of other comparable crop value chains in specific regions. The implicit suggestion that tobacco alone causes such issues (although potentially accurate) is often under-evidenced.…”
Section: Existing Approaches To Researching Tobacco Productionmentioning
confidence: 99%
“…(Research has shown that tobacco company efforts to “green” their supply chains started in the 2000s.) 27 These seven companies all mentioned their support for or promotion of sustainable agricultural practices among farmers (e.g., crop rotation, soil mulching, water conservation, and pesticide minimization). RAI was the only company to put a dollar figure to this support, noting that its subsidiary, Santa Fe Natural Tobacco Company, had provided over $190,000 to the Carolina Farm Stewardship Program to “promote sustainable farming.” All of the multinational tobacco companies and one US company (PM USA) also discussed their financial support for reforestation programs that replaced trees cut down and used for fuel in curing tobacco leaves.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy has been used in high [97][98][99] and lower and middle income 68 100 101 countries to avoid stricter regulations on smoking in public places, 10 14 17 102 tobacco advertising, 9 17 102 103 health warning labels 17 104 and tobacco farming and labour practices. [105][106][107] The earmarked tobacco taxes for tobacco control programmes provided much needed financial assistance to combat industry opposition and effectively promote, monitor, enforce and create awareness about smoke-free environments and TAPS restrictions. The Health Ministry consistently made inspections at restaurants and bars even at night time to enforce the law, which are important challenges in LMICs, 67 101 even in places with high-level compliance.…”
Section: Discussionmentioning
confidence: 99%